A) C(-1,0) B) D(0,-1) C) A(0,1) D) E(0,0)
A) EA=1/2 B) EG=1 C) EF=1 D) FG=1
A) x+y2=1 B) x2+y2=1 C) x2+y=1 D) x2-y2=1
A) 2 cm B) 3 cm C) 4 cm D) 1 cm
A) 3 cm B) 4 cm C) 1 cm D) 2 cm
A) (x-1)2+(y-1)2=(3)2 B) (x+1)2+(y-1)2=(3)2 C) (x+1)2+(y+1)2=(3)2 D) (x+1)2+(y-1)2=(2)3
A) x2.y2=1 B) x2+y2=-1 C) x2+y2=1 D) x2-y2=1
A) Reemplazar el valor de "x" y despejar "y". B) Reemplazar el valor de "x" en la ecuación x2+y2=1 y despejar "y". C) Reemplazar el valor de "x" en la ecuación x2+y=1 y despejar "y". D) Reemplazar el valor de "x" en la ecuación x2+y2=1.
A) tan30°=1 B) cos30°=1/2 C) sen30°=1/2 D) cot30°=1
A) cosα=ca/h B) senα=co/h C) cotα=1/co D) tanα=co/ca |